Feeding ecology of primates in Pandam wildlife park, Plateau State, Nigeria. (2018)
Primates are ecologically flexible and generalist feeders yet selective in choice of diet. Insufficient information on the plants consumed by primates hinders appropriate and deliberate conservation measures. I therefore seek to identify the plants species, dominant part consumed in Pandam Wildlife Park (PWLP). Direct observation method was adopted along 2km line transect to record food plants species and part consumed by primates for a period of 6 months. Proximate composition of food plants were determined using standard procedures. Data were analyzed using descriptive statistic and ANOVA at (p<0.01). Feeding sites were identified along riparian strata, savanna woodland and the swampy strata and four primates species belonging to one family (Cercopithecidae) were encountered, which include Cercopithecus mona, Erythrocebus patas, Papio anubis and, Chlorocebus tantalus, all primates were observed to feed in group. Seventeen food plants beonging to 14 families, one grass species (Andropogon gayanus), four invertebrates (Lumbrucis terrestris, Eurymerodesmus spp and Chinocectes opilio) and two crop plants (Zea mays and Sorghum vulgare) were identified. Plant parts consumed by primates include fruit, (75%) and leaves (25%). Among the food plant species, the highest crude proteins (11.86±0.07a), fats/oil (13.57±0.06a), ash (10.67±0.03a), moisture (13.63±0.07a), and crude fiber (27.85±0.48a) where obtained in Piliostigma thonningii, Rafia sundanica, Piliostigma thonningii, Stryhtinos spinose, and Tamarindus indica. Primates in the study area fed on variety of food items, predominantly on fruits irrespective of the season. Their frugivorous tendency has far ranching ecological implication with attendant effect on seed dispersal, seed treatment, seed predation, food predation, food competition, food provision, food scarcity among other sympatric animals that have fruits constituting a portion of their diet.